Robust stabilization of MIMO systems in finite/fixed time. (19th January 2015) - Polyakov, A.; Efimov, D.; Perruquetti, W.
Summary: The control design problem for finite‐time and fixed‐time stabilizations of linear multi‐input system with nonlinear uncertainties and disturbances is considered. The control design algorithm based on block decomposition and implicit Lyapunov function technique is developed. The robustness properties of the obtained control laws with respect to matched and unmatched uncertainties and disturbances are studied. Procedures for tuning of control parameters are presented in the form of linear matrix inequalities. Aspects of practical implementation of developed algorithms are discussed. Theoretical results are supported by numerical simulations. Copyright © 2015 John Wiley & Sons, Ltd.